2016
DOI: 10.1038/srep39924
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Function of Peripherally Induced Regulatory T Cells in Hosts at High Risk of Graft Rejection

Abstract: Regulatory T cells (Tregs) are crucial for allograft survival. Tregs can be divided into thymus-derived natural Tregs (tTregs) and peripherally-derived induced Tregs (pTregs). Here, we determine whether the suppressive function of Treg subsets is hampered in hosts who are at high risk for rejecting their graft. To induce graft beds that promote high risk of transplant rejection, intrastromal corneal sutures were placed two weeks prior to the transplant procedure in mice. We demonstrate that in high-risk recipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 40 publications
1
54
0
Order By: Relevance
“…status of Tregs demonstrates significant plasticity, and is determined in part by cues from their microenvironment. 23 We note that IL-10 has been reported to expand Foxp3 + Tregs, to promote CTLA-4 expression by Tregs and increase their suppressive function. 23 We note that IL-10 has been reported to expand Foxp3 + Tregs, to promote CTLA-4 expression by Tregs and increase their suppressive function.…”
Section: Il-10 Is a Key Factor In Suppressing Ifn-γ And Tnf-α-inducmentioning
confidence: 74%
See 3 more Smart Citations
“…status of Tregs demonstrates significant plasticity, and is determined in part by cues from their microenvironment. 23 We note that IL-10 has been reported to expand Foxp3 + Tregs, to promote CTLA-4 expression by Tregs and increase their suppressive function. 23 We note that IL-10 has been reported to expand Foxp3 + Tregs, to promote CTLA-4 expression by Tregs and increase their suppressive function.…”
Section: Il-10 Is a Key Factor In Suppressing Ifn-γ And Tnf-α-inducmentioning
confidence: 74%
“…Previous work from our group has shown that Tregs derived from both low-risk and high-risk corneal allograft recipients effectively suppress the proliferation of effector CD4 + CD25 − T cells, although Tregs derived from low-risk hosts exhibit 20% more suppressive capacity relative to Tregs from high-risk hosts 23. Indeed, we show that both Tregs from low-risk and high-risk hosts are effective in protecting CEnCs, with a greater cytoprotective capacity demonstrated by Tregs derived from low-risk hosts.…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…This differentiation has permitted studies evaluating these distinct Treg subsets in a variety of immunopathologies. In the current study, we used a mouse model of corneal transplantation 17) 21) 22) to delineate the differential function and susceptibility of tTregs and pTregs from allograft recipients, including healthy (low-risk) hosts with normal immune homeostatic mechanisms who develop allotolerance naturally and ʻhigh-riskʼ hosts with inflamed graft beds who are prone to swift rejection of their transplants 22) . Our study had clearly showed impaired function of pTregs, but not tTregs, mediates the loss of immune tolerance and promotes allograft rejection 22) .…”
Section: Regulatory T-cell Therapy For Corneal Transplantationmentioning
confidence: 99%